A regulação jurídica do mercado fintech - Teixeira, Juliano Puchalski (Universidade do Vale do Rio dos Sinos, 2020)
The thesis’ theme is the Fintech market, which imposes challenges to the legal system, being that the reason why this paper addresses its regulation. The research problem is limited to the way in which Fintechs can actively participate in legal regulation, through the exercise of self-regulation, in order to establish successful communication with representatives of the public power, in an environment marked by the plurality of rules and actors. The general objective is to understand the structure of Fintechs, the risks of their disruptive potential, and then to guide the self-regulatory strategy, which must be influenced by the legal system, in order to serve public interests. The thesis is divided into two parts. The first adopts the empirical methodology, to understand the characteristics of the market, the amounts invested, the activities developed, its leading companies. Then, the exam focuses on the theory of disruption and the risks that may occur. In the second part, using the comparative law methodology, the objective revolves around regulation. Teubner's social constitutionalism and the theory of liquid authority, by Nico Krisch and Julia Black, are adopted as the theoretical matrix. The thesis defends that the negative externalities of Fintechs are confronted by self-regulation, whose strategy must be influenced by the other actors of the legal system, in a hybrid constitution process. Afterwards, the characteristics of four innovative regulatory methods that propose to carry out the hybrid constitution are examined, as are their recent results. The research concludes that the market’s regulatory activity must be carried out in a shared way, with an emphasis on regulated self-regulation, based on constant learning. The knowledge of better regulations, their instruments, risk management, the definition of the regulatory strategy, demand a wide, transparent and justified debate, in which decisions are marked by the constant possibility of revision.
Keywords: Fintech; Regulação; Autorregulação; Regulation; Self-regulation; Better regulations; ACCNPQ::Ciências Sociais Aplicadas::Direito